Critical Assessment of the High Carrier Mobility of Bilayer In2O3/IGZO Transistors and the Underlying Mechanisms. (19th January 2023) - Guo, Min; Ou, Hai; Xie, Dongyu; Zhu, Qiaoji; Wang, Mengye; Liang, Lingyan; Liu, Fengjuan; Ning, Ce; Cao, Hongtao; Yuan, Guangcai; Lu, Xubing; Liu, Chuan
Abstract: High‐performance bilayer In2 O3 /IGZO thin‐film transistors (TFTs) fabricated by pulsed laser deposition are reported. The TFTs exhibit an on/off current ratio of 10 9, a reversed subthreshold slope (ss) of 0.08 V dec −1, and a high saturation mobility of 47.9 cm 2 V −1 s −1 . The reliability of the mobility values is critically validated and assessed by four‐probe measurements, the transfer‐length method, and the temperature‐dependence. X‐ray photoelectron spectra are combined with C–V measurements to characterize the interface, and the results show that a two‐dimensional electron gas (2DEG)‐like state accumulates at the In2 O3 /IGZO interface. However, this state only forms in the subthreshold region and does not cause the high carrier mobility in the region above the threshold. Instead, the enhanced carrier mobility results from the intrinsic high mobility of the In2 O3, the smooth surface, and the low‐defect states in the In2 O3 /IGZO bilayer with a good percolation transport path. Abstract : The reliability of mobility values of In2 O3 /IGZO bilayer thin‐film transistors (TFTs) and the reasons for their high mobility are investigated. In particular, the role of the interface two‐dimensional electron gas (2DEG) in the carrier transport of bilayer TFTs is evaluated.